ENTREPRENEURSHIP AS NEW APPROACH TO INCREASE BUSINESS PERFORMANCE: EMPIRICAL STUDY ON CHILI DAN RICE FARMING AT SLEMAN REGENCY YOGYAKARTA - Darmadji Darmadji (UNEJ e-Proceeding, 2012)
ENTREPRENEURSHIP AS NEW APPROACH TO INCREASE BUSINESS PERFORMANCE: EMPIRICAL STUDY ON CHILI DAN RICE FARMING AT SLEMAN REGENCY YOGYAKARTA